Osteonecrosis of the jaw in patients with inflammatory bowel disease treated with tumour necrosis factor alpha inhibitors. Issue 3 (March 2020) - Brijs, K.; Miclotte, I.; Vermeire, S.; Darche, V.; Politis, C.
Abstract: Previous reports have suggested a possible association between tumour necrosis factor alpha (TNF-α) inhibitors, used in the treatment of immune-mediated inflammatory diseases, and medication-related osteonecrosis of the jaw (MRONJ). However, a comprehensive assessment of the frequency and severity of MRONJ caused by these agents is lacking. The aim of this cohort study was to investigate the occurrence of MRONJ in a population of patients with inflammatory bowel disease (IBD) treated with TNF-α inhibitors at a tertiary care medical centre. A total of 2701 IBD patients under current or former treatment with TNF-α inhibitors were identified in an IBD registry covering the period 1994–2018. These patients were cross-matched with all patients diagnosed with MRONJ. This resulted in three patients with a definite diagnosis of MRONJ, without concomitant treatment with bisphosphonates. All three patients required surgical treatment with sequestrectomy. Mucosal healing occurred at 4–15 months and one patient developed recurrence. In conclusion, this study identified and described anti-TNF-α-related MRONJ occurring in a large cohort of IBD patients, and reported the severity and treatment strategies used.